Highly pathogenic avian influenza virus (H5N5) detected in an Atlantic walrus (Odobenus rosmarus rosmarus) in the Svalbard Archipelago, Norway, 2023 - Postel, Alexander; Gremmel, Nele; Lydersen, Christian; Kovacs, Kit M.; Schick, Luca A.; Siebert, Ursula; Nymo, Ingebjørg H.; Becher, Paul (Emerging Microbes & Infections, 2025)
We present the first documented case of highly pathogenic avian influenza virus (HPAIV) subtype H5N5 in an Atlantic walrus (Odobenus rosmarus rosmarus). The animal was found dead in Svalbard, Norway, in 2023. Sequence analysis revealed the highest genetic similarity with virus isolates from different avian hosts.